Defining Influencing Success Factors In Global Software Development (GSD) Projects - Dr. Andreas Drechsler, Anna Yuliarti Khodijah , (PROCEEDING IC-ITECHS 2014, 2014)
Context:Â Â Global Software Development (GSD) continues to experience substantialgrowth of trend concerning the development of software virtually distributed throughout different countries. GSD has several advantages as opposed to the collocated development, but there are also a number of challenges. As a project manager, we should know these and find ways to successfully manage the project virtual team. Objective: This paper is to delineate the study to define which factors influence the success of GSD projects. Method: Using the literature review method, 5 GSD success factors-related literature were selected and reviewed to distinguish the relevant success factors as being reported in the literature. Results:Â Â The study Â indicated Â thatÂ there Â are Â different Â opinions Â in Â consideringÂ which Â factors Â are Â most important to GSD project success. Some experts see the âpeopleâ side of the team would contribute Â most, Â but Â others Â still Â think Â that Â theÂ âgeographicalâ Â sides Â (language Â barriers, culture, distance, time difference) are the most dominant factors.Â Conclusion: The results obtained in this paper addressed two aspects; one showing that the challenges of GSD is changing, thus making the influencing factors changing too. Second, this paper can serve as a guide and insight for project managers to better understand how to manage and coordinate a virtual talented team across different countries.